Kontribusi Mazhab Teologis Mu'tazilah Dalam Perkembangan Sastra Arab Era Aabbasiyah Studi Analisis Kritis Historis: The Contribution of the Mu'tazilah Theological School to the Development of Arabic Literature During the Abbasid Era: A Critical Historical Analysis. - Zulhelmi, Zulhelmi; binti Haji Abdullah, Hajjah Rafidah; binti Mohamad Suhane, Shuhaida Hanim; Batubara, Ashwaq Ismail S; Delami (An-Nahdah Al-'Arabiyah, 2024)
This research aims to reveal the contributions of the Mu'tazilah school of thought to the development of Arabic literature during the Abbasid dynasty. This study is important to ensure that today's generation of Muslims does not deny the achievements of Mu'tazilah writers of the Abbasid era due to theological differences. The main issue addressed in this research is the various forms of Mu'tazilah's contributions to the development of Arabic literature during the Abbasid dynasty. The reason for focusing on the Abbasid period is that during this time, the Mu'tazilah held a special place in the royal court, with Caliph al-Ma'mun even making Mu'tazilah the official ideology of the kingdom. This research is qualitative in nature, with data collected through library research. The theoretical framework employed is historical criticism theory, as the study's object involves historical facts of the Islamic golden age. The researcher concludes that the Mu'tazilah made significant contributions to the development of Arabic literature. These contributions are evident in the emergence of prominent literary figures and critics such as al-Jahiz, Abu Hayyan al-Tawhidi, and al-Qadi al-Jurjani. Moreover, they also contributed to the creation of new literary genres, including al-Munadharah, al-Jadal, al-Mawa'id, and al-Adab al-Dini. In light of these contributions, it is hoped that Muslim scholars in the field of Arabic language and literature will acknowledge these historical achievements. تهدف هذه الدراسة إلى الكشف عن إسهامات مذهب المعتزلة في تطور الأدب العربي خلال فترة الخلافة العباسية. تعتبر هذه الدراسة مهمة حتى لا تنكر الأجيال المسلمة اليوم الإنجازات التي حققها أدباء المعتزلة في العصر العباسي بسبب الاختلافات المذهبية اللاهوتية. تتمثل المشكلة الرئيسية في هذه الدراسة في أشكال إسهامات المعتزلة المختلفة في تطور الأدب العربي خلال فترة الخلافة العباسية. والسبب في التركيز على هذه الفترة هو أن المعتزلة كانوا يحظون بمكانة خاصة في البلاط الملكي خلال هذه الفترة، حيث جعل الخليفة المأمون مذهب المعتزلة أيديولوجية رسمية للمملكة. هذه الدراسة نوعية، وتم جمع البيانات من خلال البحث المكتبي. الإطار النظري المستخدم هو نظرية النقد التاريخي، لأن موضوع الدراسة يشمل الحقائق التاريخية للعصر الذهبي الإسلامي. وخلص الباحث إلى أن المعتزلة قدموا إسهامات كبيرة في تطور الأدب العربي. تتجلى هذه الإسهامات في ظهور شخصيات أدبية ونقاد بارزين مثل الجاحظ وأبو حيان التوحيدي والقاضي الجرجاني. علاوة على ذلك، أسهموا أيضًا في إنشاء أنواع أدبية جديدة، مثل: المناظرة، الجدل، المواعظ والأدب الديني. في ضوء هذه الإسهامات، يُأمل أن يعترف الباحثون المسلمون في مجال اللغة والأدب العربي بهذه الإنجازات التاريخية. Penelitian ini bertujuan untuk mengungkapkan kontribusi yang telah diberikan oleh mazhab teologis Islam mu’tazilah terhadap perkembangan sastra Arab pada masa dinasti Abbasiyah. Penelitian ini penting diungkapkan supaya generasi umat Islam hari ini tidak mengingkari dan terkesan menutup mata atas prestasi yang pernah diraih oleh para sastrawan Mu’tazilah era Abbasiyah, akibat dari perbedaan mazhab teologis. Permasalahan yang diajukan dalam penelitian ini adalah apa saja bentuk kontribusi mazhab teologi Mu’tazilah terhadap perkembangan sastra Arab masa dinasti Abbasiyah. Alasan penelitian ini dibatasi pada masa dinasti Abbasiyah karena pada masa itu kaum Mu’tazilah pernah mendapatkan tempat yang istimewa di istana, bahkan pada masa khalifah al-Ma’mun, Mu’tazilah menjadi ideologi resmi kerajaan. Adapun jenis penelitian ini adalah penelitian kualitatif. Sedangkan metode pengumpulan datanya dilakukan melalui penelitian perpustakaan. Teori yang digunakan adalah teori kritik sejarah karena objek kajiannya merupakan fakta-fakta historis masa lalu umat Islam di masa kejayaannya, Abbasiyah. Peneliti menemukan kesimpulan bahwa mazhab teologis Mu’tazilah pada masa dinasti Abbasiyah telah memberikan kontribusi yang nyata terhadap perkembangan sastra Arab. Kontribusi tersebut terlihat pada kemunculan tokoh-tokoh sastrawan dan kritikus sastra besar dan berpengaruh, di antaranya yang paling terkenal adalah al-Jahiz, Abu Hayyan al-Tauhidy dan al-Qadhi al-Jurjani. Selain itu, mereka juga turut menciptakan genre sastra baru, seperti: al-muna>d}arah, al-jadal, al-mawa>’id} dan al-adab al-di>ni. Atas kontribusi ini, diharapkan para generasi umat Islam yang bergelut dalam bidang ilmu bahasa dan sastra Arab untuk bisa mengapresiasi atas prestasi para sastrawan Mu'tazilah tersebut dan tidak berupaya untuk menguburkannya hanya karena perbedaan mazhab teologis.   Kata Kunci: Sastrawan Mu’tazilah, Dinasti Abbasiyah, dan Analisis Kritis Historis